Synthesis and characterization of a novel extra large pore aluminophosphate molecular sieve, NCL-6 - Venkatathri, N (Journal of the Indian Chemical Society, 2005)
A novel extra large pore aluminophosphate molecular sieve NCL-6, has been prepared and characterized by various techniques such as XRD, SEM, TG/DTA, carbon and nitrogen analysis, FT-IR and MAS NMR are reported. X-Ray diffraction pattern shows that the synthesized sample is crystalline and have novel structure. SEM analysis indicate the phase purity and having granules morphology with 3 x 5 mum particle size. FT-IR spectrum in the framework region shows that the sample is similar to the other known aluminophosphates. TG/DTA shows that the sample losses 30.45% due to the loss of water and organic molecules. Aluminium and phosphorous NMR shows that the presence of four different aluminium and three different phosphorous sites. The NMR are similar to VPI-5, NCL-2 and NCL-3.